Design and Fabrication of a 2.4 GHz Right Hand Circular Polarized Micro-Strip Patch Antenna: 2.4 GHz Right Hand Circular Polarized Micro-Strip Patch Antenna - Ahmad, Mansoor; Khalil, Fazli A. (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2022)
In this paper, we present a single feed circularly polarized microstrip patch antenna operating at 2.4 GHz WLAN frequency. A typical microstrip patch antenna is fabricated on a metal coated dielectric substrate where the metallic antenna patch is defined on the top of the substrate, whereas the bottom of the substrate acts as a ground plate. These antennas are typically used for civil and military communication purposes. Before fabrication, the presented antenna was first designed, simulated and optimized in CST Microwave studio. The circular polarization was achieved by perturbation of the edges, making the design optimization a bit challenging. The simulated and measured return loss of the proposed antenna is -27 dB and -13.34dB, respectively. Whereas, the gain came out to be 6 dB. The obtained results show that the presented antenna has the quality of right hand circular polarized antenna.